Simulation of the 2018 Tsunami Due to the Flank Failure of Anak Krakatau Volcano and Implication for Future Observing Systems. Issue 14 (16th July 2020) - Mulia, Iyan E.; Watada, Shingo; Ho, Tung‐Cheng; Satake, Kenji; Wang, Yuchen; Aditiya, Arif
Abstract: Motivated by the unwarned tsunami disaster caused by the flank collapse of the Anak Krakatau volcano on 22 December 2018, we used a landslide tsunami model to explore potential tsunami observing and warning systems for the region. With the estimated volume of 0.24 km 3 and the relatively short duration (~3 to 5 min), the landslide of the volcanic edifice in the southwest sector triggered a tsunami of higher than 40 m in the vicinity. The tsunami, however, attenuated rapidly as it propagated away from the generation area, resulting in lower than 2 m wave heights at tide gauges around the Sunda Strait. Using the tsunami model, we demonstrated the capability of a ship height positioning method to detect the tsunami of amplitude ~20 cm associated with the event. Furthermore, assimilating the tsunami current velocity observed by high‐frequency oceanographic radars can produce accurate forecasts of coastal tsunami heights. Plain Language Summary: The tsunami on 22 December 2018 claimed hundreds of lives across the Sunda Strait regions of Indonesia. Unlike typical tsunamis, this silent tsunami was caused by the activity of Anak Krakatau volcano. This paper proposes new tsunami observation and warning systems for such a tsunami by modeling the generation and propagation processes. Although the source characteristics are constrained using limited data, that is, satellite images, the model can reproduce tsunami waveforms recorded at tide gauges and flow depths measured at specified regions. We then perform numerical experiments to assess the performance of potential tsunami observing systems based on high‐frequency oceanographic radars and ship‐height positioning. The experiment suggests that both systems can be viable future tsunami observations in the region. Key Points: The study models the tsunami generation and propagation processes associated with the Anak Krakatau volcano We validate our model against tsunami waveforms at tide gauges and flow depths Based on the model, tsunami observing systems using oceanographic radars and ship height positioning are suitable for the region